A study of location selection for large agricultural wholesale markets under the perspective of modern circulation - Guizhe Xin; Yuqing Tang (PLoS ONE, 2026)
This study investigates the critical challenges associated with location selection for large-scale Agricultural Product Wholesale Markets (APWMs) under the traditional circulation model. It identifies and elaborates on the evolving characteristics of circulation stakeholders, supply chains, distribution channels, organizational structures, and external environments during the transition from traditional to modern circulation systems. In response to the demands of modern circulation, a comprehensive location selection evaluation framework is proposed, integrating five key criteria: location, planning, transportation, land use, and urban compatibility. Elastic and rigid evaluation standards are established according to the nature of each criterion. The framework innovatively integrates national territorial and spatial planning, road traffic planning, industrial development planning, and urban big data resources through Geographic Information System (GIS) technology, consolidating these into a unified database. To determine comprehensive weights for different functional types of APWMs, the normalized linear aggregation method is applied to combine weights derived from the Analytic Hierarchy Process (AHP) and the entropy weight method, enabling an analysis of correlation and contribution levels. Furthermore, this study introduces an innovative application of the Genetic Algorithm (GA), implemented in Python, to re-optimize the integration of subjective and objective weights through iterative computation until convergence, thereby enhancing the accuracy of comprehensive weight estimation and validating the location selection outcomes. A case study demonstrates the successful development of a five-phase location selection methodology—region screening, scope delineation, data analysis, weight optimization, and comprehensive evaluation—enabling both quantitative ranking and recommendation of candidate location and the optimal solution was ultimately selected from seven candidate schemes. This research provides practical guidance for location selection of large-scale APWMs within modern circulation contexts and offers methodological insights applicable to urban logistics planning and the siting of other large-scale infrastructure facilities.